The Protective Effect Of Rambutan Honey On Macroscopic And Microscopic Examination Of Pancreas Rattus norvegicus Induced By Traditional Alcoholic Beverages Ciu - Fitria Diniah Janah Sayekti; Pramesti Kirana Putri (Al-Hayat: Journal of Biology and Applied Biology, 2025)
The traditional ciu alcoholic beverages is a drink made from distilled sap and sticky tape. Ciu is a type of drink that has an alcohol content of 25%. Alcoholic beverages will be toxic if consumed in excess. The pancreas is one of the organs that undergoes a process of damage when toxicmaterials or metabolites accumulate in the organ. Rambutan honey is a natural ingredient that contains flavonoid compounds. Flavonoids act as antioxidants which can reduce damage to pancreatic cells due to toxic substances. The aim of this study was to determine the protective effect of rambutan honey on the macroscopic and microscopic examination of white rats (Rattus norvegicus) induced by traditional ciu alcohol. This research is experimental with 5 treatment groups including 1 control normal, 1 control negative and 4 ciu and honey treatments. Pancreatic tissue was observed macroscopically for color and texture. Microscopic observations were observed in the form of degeneration and necrosis. The microscopic results showed that there was a color difference between the control group and the alcohol-induced honey treatment group. The results of microscopic observations were known to show degeneration and necrosis in the positive group and the treatment group. The results of the study based on the ANOVA test obtained <0.05. Based on the Anova test and Duncan test it can be concluded that rambutan honey has a protective effect on the pancreatic histopathology of white rats (Rattus norvegicus) in the form of normal cells and degenerated cells in groups K2 and K3